Development and Utilisation of the Chinese Version of Professional Attitude Scale for Nurses: Two Cross‐Sectional Studies - Siai Zhang; Bingyan Zhao; Cuiwei Lai; Chunmei Zhang; Zhangyi Wang; Yajun Zhang; Jiajia Li; Xuechun Li; Sina Zhang; Tiane Fa (Nursing Open, 2025)
ABSTRACT Aim To translate and assess the psychometric characteristics of the Chinese version of the Professional Attitude Scale for Nurses (PASN‐C) and utilise it to investigate the present status and associated factors of professional attitude among Chinese nurses. Background Assessing professional attitude is a crucial aspect of nursing professionalism. However, there is a significant gap in the field as no reliable instrument exists in China to assess nurses' professional attitudes. Methods The PASN‐C was created by adapting the Brislin translation model. The participants hailed from 11 hospitals in Tianjin, China. Two cross‐sectional studies were performed, in which a convenience sampling method was used to survey 877 participants (first study) to assess the validity and reliability of the PASN‐C; furthermore, 1154 participants (second study) were surveyed to analyse the current status and associated factors of the professional attitudes of Chinese nurses. Results The PASN‐C maintained 38 items and 8 factors, which explained 60.540% of the variance. The item‐level content validity index (0.860–1.000), dimension‐total score correlation coefficient (0.622–0.766), and Cronbach's alpha coefficient (0.943) indicated PASN‐C had good validity and reliability. The score of PASN‐C was 136.16 ± 15.48. Male, tertiary hospitals, specialty hospitals, high‐income, obstetric nurses and specialist nurses were associated with a higher professional attitude. Conclusions The PASN‐C is a reliable and valid instrument that can be utilised to assess Chinese nurses' professional attitudes. Furthermore, this study suggests that more attention should be paid to associated factors to improve nurses' professional attitudes. Implications for the Profession The PASN‐C can be an effective tool to assess the professional attitude of Chinese nurses. Furthermore, nursing administrators, educators and clinical nursing practitioners could strengthen training in the dimensions of ‘autonomy of clinical judgment’, ‘work‐related independence’ and ‘enhancement of nursing education’ to improve the professional attitude of nurses. Reporting Method This study followed and reported according to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) reporting guidelines. Public Contribution Researchers received the data from the managers of each participating hospital after distributing the electronic survey to the participants.